Evaluation of hearing preservation in adults with a slim perimodiolar electrode - Ludwig, Sonja; Riemann, Niklas; Hans, Stefan; Christov, Florian; Ludwig, Johannes Maximilian; Saxe, Judith; Arweiler-Harbeck, Diana (European archives of oto-rhino-laryngology and head & neck, 2022)
Numerous endeavors have been undertaken to preserve hearing in cochlear implant (CI) patients. Particularly, optimization of electrode array design aims at preservation of residual hearing (RH). This study examines whether a slim perimodiolar (PM) electrode array could bear the capability to preserve hearing.
Online veröffentlicht am 08. April 2021
Gesehen am 09.01.2023